Efektivitas Media Audiobook Berbasis Digital Dalam Meningkatkan Motivasi Belajar Siswa Tunanetra di Sekolah Inklusi - Naia Anindya Dara; Cipto Hadi (Jurnal Pendidikan Tuntas, 2026)
Low learning motivation among students with visual impairments is often associated with limited access to learning materials that match their sensory characteristics. This study employed a literature review method to examine published scholarly articles related to the use of digital audiobook-based learning media in the educational process. The literature search was conducted through Google Scholar using the keywords “digital talking book,” “audiobook,” “learning motivation,” “visual impairment,” and “inclusive education,” and was expanded by utilizing the “related articles” feature. The selected articles were limited to publications from 2015–2025 and consisted of peer-reviewed academic journal articles, resulting in 14 relevant studies that met the research criteria. The selected articles were further analyzed using a meta-synthesis approach to identify patterns of findings and trends regarding the impact of digital audiobook-based media on the learning motivation of students with visual impairments. The results indicate that the use of digital audio media, including audiobooks and Digital Talking Books (DTB), can enhance students’ learning motivation by increasing participation, improving material retention, and fostering deeper conceptual understanding. Presenting learning materials in audio format also facilitates easier access to information, provides a more flexible and independent learning experience, and aligns with the auditory learning needs of students with visual impairments. However, the implementation of such media still faces several challenges, including limitations in technological infrastructure and the uneven distribution of digital learning content. Overall, digital audiobook-based media demonstrate strong potential as an inclusive learning tool for improving the learning motivation of students with visual impairments.